European lobbies: a comparative study of the professional profiles of lobbyists in Spain and France - Guerra-Heredia, Sergio; Lobillo-Mora, Gema María; Martín-Martín, Penélope Noelia; Espino González, Jesús (Frontiers in Political Science, 2024)
This research consists of carrying out a comparison of professional lobbyists in Spain and France, using three broad areas of data: socio-geographical, academic, and professional. The objectives set are aimed at a general and specific comparison to obtain a typical profile of the professionals of both countries. To this end, an exploratory methodology has been used, with a multivariate statistical analysis, completed with a descriptive analysis of an inductive nature, through a sample of 1,000 professional lobbyists in Spain and France in 2024. The results obtained provide a profile of lobbyists in Spain and France based on their social, academic, and professional nature. The main conclusion is that in these two countries these professionals classify their work as being in the field of “Public Affairs,” their academic background is mainly in Law and Political Science, and they live in large urban areas.
Keywords: Grupos de presión; Lobbying; Pressure groups; Spain; France; Public affairs; Influence; Training; Professional profile